A Fuzzy Logic Control Strategy for Doubly Fed Induction Generator for Improved Performance under Faulty Operating Conditions - G. Venu Madhav; Y. P. Obulesu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, decouple PI control for output active and reactive powers which is the common control technique for power converter of Doubly Fed Induction Generator (DFIG) is presented. But there are some disadvantages with this control method like uncertainty about the exact model, behavior of some parameters or unpredictable wind speed and tuning of PI parameters. To overcome the mentioned disadvantages a fuzzy logic control of DFIG wind turbine is presented and is compared with PI controller. To validate the proposed scheme, simulation results are presented, these results showed that the performance of fuzzy control of DFIG is excellent and it improves power quality and stability of wind turbine compared to PI controller. The Fuzzy logic controller is applied to rotor side converter for active power control and voltage regulation of wind turbine. The entire work is carried out in MATLab/Simulink. Different faulty operating conditions are considered to prove the effective implementation of the proposed control scheme.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.5966